Action mode of ursolic acid as a natural antioxidant and inhibitor of superoxide dismutase: In vitro and in silico study - Ara Deani Somantri; Dikdik Kurnia; Achmad Zainuddin; Hendra Dian Adhita Dharsono; Mieke Hemiawati Satari (Wolters Kluwer Medknow Publications, 2021)
Recently, the antioxidant is applied for the teeth bleaching treatment as an alternative of toxic material of hydrogen peroxide that is used in teeth bleaching. One of natural sources antioxidant is Uncaria gambir those containing active antioxidant agents. To be applied as a new bioactive constituent in teeth bleaching treatment, a preexperimental study is performed. The aim of the study is to identify the antioxidant constituent of U. gambir and predict their activity including action mode as an inhibitor of enzyme superoxide dismutase (SOD) through in vitro and in silico method. Combination of chromatography methods and spectroscopic analysis is used for isolated bioactive antioxidant constituent. The antioxidant activity was evaluated by in vitro assay against diphenylpicrylhydrazyl (DPPH) and SOD, respectively, while prediction of action mode of the active compounds as SOD-mutant enzyme inhibitor was conducted by in silico study using AutoDock 4.2 program. Antioxidant of ursolic acid was isolated from U. gambir with inhibitory concentration50 values 1721 ± 30.6 and 392 ± 53.57 μg/mL, respectively, against DPPH and SOD. By in silico study presented that ursolic acid inhibited SOD enzyme with a binding affinity of − 5.4 kcal/mol those higher than a quercetin as a positive control. The ursolic acid was identified as a potential natural antioxidant with potentially activity to inhibit SOD mutant.